Estudos sobre o uso de pentacloreto de nióbio na síntese de derivados de tetra-aril-1,4 di-hidropirrol [3,2-B] pirroles - Baldacim, Gabriel Baldo [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The main objective of this work was to evaluate the use of niobium pentachloride, element which Brazil has the world's largest reserves, in multicomponent reactions for the synthesis of organic compounds with potential application as sensitizing dyes in hybrid photovoltaic devices, investigating the application of NbCl5 as a Lewis acid in multicomponent reactions between benzaldehyde derivatives, aniline and vicinal diketones for the synthesis of substituted tetra-aryl-1,4-dihydropyrrolo[3,2-b]pyrroles derivatives, verifying the effect of the molar concentration of NbCl5. The analysis of the obtained results, and the comparison with the data found in the literature, allowed us to demonstrate the efficiency of niobium pentachloride in the multicomponent reaction. Data obtained through photophysical characterizations showed us the efficacy of tetra-aryl-1,4-dihydropyrrolo[3,2-b]pyrroles derivatives as sensitizing dyes in electronic devices

O estudo principal deste trabalho foi avaliar a utilização do pentacloreto de nióbio, o qual elemento central, o Brasil possui as maiores reservas mundiais, em reações multicomponentes para o desenvolvimento de compostos orgânicos com potencial aplicação como corantes sensibilizadores em dispositivos fotovoltáicos híbridos, investigando a aplicação do NbCl5 como ácido de Lewis em reações multicomponente entre derivados de benzaldeído, anilina e dicetonas vicinais para a síntese de derivados tetra-aril-1,4-di-hidropirrol[3,2-b]pirroles substituídos, verificando detalhadamente o efeito da concentração molar de NbCl5. A análise dos resultados obtidos, em comparação com os dados encontrados na literatura, nos permitiu demonstrar a eficiência do pentacloreto de nióbio na reação multicomponente. Dados obtidos através de caracterizações fotofísicas nos mostram a eficácia dos derivados de tetra-aril- 1,4-di-hidropirrol[3,2-b]pirrol como corantes sensibilizadores em dispositivos eletrônicos
Keywords: Cloretos; Compostos de nióbio; Reações quimicas; Corantes